Salivary cytomegalovirus excretion in children in daycare centers and home care facilities in Japan. Issue 12 (9th August 2019) - Watanabe, Masahiro; Torigoe, Sadayoshi; Ito, Masahiro; Negoro, Manami; Suga, Shigeru
Abstract: Cytomegalovirus (CMV) is the most common cause of congenital viral infection in developed countries. The incidence of in utero infection is high in pregnant women who are CMV antibody negative. An important infection route is in contact with children who attend daycare centers (DCCs). However, there are few reports on CMV excretion in children at DCCs in Japan. Saliva samples were collected twice during a 6‐month interval from children attending one of two DCCs (DCC1 and DCC2 groups) and from those receiving home care (HC group). The samples were used to quantitatively evaluate CMV using real‐time polymerase chain reaction and to determine glycoprotein B (gB) genotypes. The percentage of subjects who demonstrated CMV excretion in either the first or second sample collection was higher in the DCC groups than in the HC group, with incidences in the DCC1, DCC2, and HC groups of 53.4% ( n = 47 of 88), 23.9% ( n = 16 of 67), and 12.7% ( n = 7 of 55), respectively. Compared with the DCC2 group, the DDC1 group had a higher incidence of CMV excretion and included more subjects with a high number of viral copies. In both DCC groups, the incidence of CMV excretion was highest in children younger than 3 years of age. In all three groups, the predominant genotypes were gB1 and gB3. Based on the higher incidence of CMV excretion in the DCC groups compared with the HC group, it is considered that CMV infection is acquired mainly in DCCs in children under the age of 3. Highlight: CMV infection is acquired mainly in DCCs in children under the age of 3.